2023
DOI: 10.2147/opth.s386222
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the 2-Year Results of Photodynamic Therapy with Aflibercept and Aflibercept Monotherapy for Polypoidal Choroidal Vasculopathy

Abstract: Purpose To compare the efficacies of photodynamic therapy (PDT) combined with intravitreal aflibercept (IVA) injections and IVA monotherapy using a treat-and-extend regimen (TAE) for treatment-naïve polypoidal choroidal vasculopathy (PCV). Patients and Methods One hundred and nine eyes treated with PDT combined with IVA (PDT+IVA group: 51 eyes) or IVA monotherapy (IVA group: 58 eyes) were assessed for 2 years. The main outcome measures included best-corrected visual acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Ranibizumab showed a complete regression rate of 25% 12 , while in our previous study, aflibercept administered once every 2 months showed a rate of 50% 13 , 14 . Brolucizumab showed a rate of 79–90% 15 , 16 , and photodynamic therapy showed a rate of over 70% 17 , 18 . Our findings demonstrated a noteworthy 50% rate of complete regression following 1 year of faricimab treatment for PCV.…”
Section: Discussionmentioning
confidence: 99%
“…Ranibizumab showed a complete regression rate of 25% 12 , while in our previous study, aflibercept administered once every 2 months showed a rate of 50% 13 , 14 . Brolucizumab showed a rate of 79–90% 15 , 16 , and photodynamic therapy showed a rate of over 70% 17 , 18 . Our findings demonstrated a noteworthy 50% rate of complete regression following 1 year of faricimab treatment for PCV.…”
Section: Discussionmentioning
confidence: 99%
“…There was little information on the incidence of atrophy after PDT for PNV. As for PCV, Miyakubo et al mentioned that the frequencies of macular atrophy expansion in combination therapy during 2 years was 33% with no significant difference compared to anti-VEGF monotherapy (26%) [ 28 ]. However, Miyata et al reported that 5-year incidence of macular atrophy was greater in initial combined PDT than in anti-VEGF monotherapy [ 21 ].…”
Section: Discussionmentioning
confidence: 99%